(untitled) (Research, Society and Development, 2025)
Introduction: Erythema multiforme is a skin condition that presents with isolated, recurrent, or persistent lesions. The herpes simplex virus is responsible for 80% of cases. Objective: This study aims to review the literature on EM associated with HSV infection since early pathology identification can direct treatment, offering benefits to the patient (with shorter hospital stays and reduced recurrences). Method: This study consists of a literature review and articles published in the Scielo and PubMed databases were used. Results and Discussion: Erythema multiforme lesions usually begin with papules that can evolve into plaques, typically with a target-shaped presentation. Prodromes such as fever, malaise, and weakness are reported. Erythema multiforme due to herpes simplex virus is a viral disease with inflammatory and autoimmune components. The lesions are free but contain DNA fragments of the pathogen. The expression of viral proteins initiates the development of lesions through the recruitment of T cells. Treatment depends on the etiology and severity of the disease, being supportive in mild cases and with antivirals, corticosteroids antihistamines, and immunomodulators in moderate to severe cases. Erythema multiforme can be recurrent, with approximately 6 episodes per year. Conclusion: Erythema multiforme is a low-incidence pathology with significant potential for severity, possibly leading to hospitalization. Studies establishing diagnostic and treatment protocols are encouraged.